Efektivitas Pemasaran Layanan Perpustakaan Online pada Masa COVID-19 di Perpustakaan Nasional Republik Indonesia - Zikrayanti Zikrayanti; Nurul Rahmi; Wahyudi Sekedang (Perpustakaan Nasional, 2023)
Online library services are a way for the National Library of Indonesia to provide the role of the library in meeting the information needs of society, especially during a pandemic. As for the formulation of the problem in the research under study, namely, how is the marketing effectiveness of online library services during the COVID-19 period at the National Library of Indonesia . This study aims to measure the marketing effectiveness of online library services during the COVID-19 period at the National Library of Indonesia, using the A-T-R theory, because this theory is a theory that can be used to see the extent of marketing effectiveness. The A-T-R theory consists of three stages, namely awareness, trial, and reinforcement. The method used in this study is descriptive quantitative by collecting data using a questionnaire which is processed in the form of percentages which are then described in the form of statements. Respondents who were involved in the research were 357 people who were registered as members of the National Library. Data collection was carried out by distributing Google Forms and this research was carried out for a month. The results of the study show that the online library services of the National Library of Indonesia are in the effective category and it was found that respondents believed in using National Library of Indonesia online library services regularly.